Acquisition in Strategic Management: The Pitfalls and Guidelines towards A Socio- Psychological Successful Outing - ORISHEDE, Felix; AKPEDE, Augustine; MADUEMEZIA, Patricia Ifeanyi (International Journal of Psychosocial Rehabilitation, 2020)
The study examined acquisition in strategic management against the background qualitatively of psychological success in their operations. The objectives were aimed at reviewing how pitfalls and guidelines have successfully enhanced. The study adopted a qualitative review of extant literature around the variables under study. The literatures revealed a nexus between acquisition of strategic management and successful outing. Also there was a binding factors of success around knowledge management practices towards a successful outing. The work established that stakeholders in corporate organizations should guide the knowledge acquision to successfully implement strategic management.